2020
DOI: 10.1002/bsd2.103
|View full text |Cite
|
Sign up to set email alerts
|

Business experience or Financial Literacy? Which one is better for opportunity recognition and superior performance?

Abstract: Recognition of useful opportunities is very crucial for small and medium‐sized enterprises' (SMEs') survival and growth in the competitive environment. However, the majority of SMEs cannot easily recognize new opportunities in the turbulent markets due to a lack of managerial competencies and knowledge. Several studies have been carried out to unleash the determinants of opportunity recognition that configure SMEs' success, but the results are disjointed. In particular, the mediating role of opportunity recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 50 publications
1
33
1
1
Order By: Relevance
“…Our research reveals that experience has an indirect influence on sustainable performance in business industry where the adaption of export marketing strategy plays a full mediating role. However, [ 21 ] demonstrated that new opportunity recognition partially mediates the link between managerial experience and sustainable performance. Matching Feurer, Schuhmacher [ 58 ] who described that adequate knowledge and experience are very crucial in building innovative products and marketing strategy.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 4 more Smart Citations
“…Our research reveals that experience has an indirect influence on sustainable performance in business industry where the adaption of export marketing strategy plays a full mediating role. However, [ 21 ] demonstrated that new opportunity recognition partially mediates the link between managerial experience and sustainable performance. Matching Feurer, Schuhmacher [ 58 ] who described that adequate knowledge and experience are very crucial in building innovative products and marketing strategy.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…It refers to the knowledge and experience of top managers/owners in international business, trading, export, import, operation, supply, and purchasing and selling. In order to know about experience of the marketing managers, we have asked five questions (adopted from Anwar, Shuangjie [ 21 ]) and Ying, Hassan [ 11 ]) if they have knowledge or experience of import/export, national and international trade experience etc.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations